Knowledge Management, Intellectual Capital, And Performance Of Branch Office Of State-Owned Banks - Hadijah, Hady Siti (Jurnal Manajemen, 2018)
The goal of this research is to determineif intellectual capital could mediate the influence of knowledge management on the branch performance offices of state-owned banks. If we compare to the ASEAN banks, the performance of state-owned banks is weak, especially in the case of operational cost efficiency depressing the potential for large profits. The low level of performance cannotbeseparatedfrom of the low performance of branch offices. BI's expectation as stipulated in the BI Regulation of 2010 is that the banking sector should perform the maximum role of branch offices because if the management of branch offices understandknow more than head officedoes.The improvement in knowledge management should be made by state-owned banks at branch offices.Beside, it is necessary that aggregation of all knowledge and employee competence that allows companies to gain competitive advantage. In my research, the method of research used is explanatory survey. Structural Equation Modeling (SEM) using LISREL was chosen to test the hypothesis.152 pieces of sample were taken from the whole state-owned banksoffices in West Java. The focus of the assessment is the branch officees of state-owned banks located in the region of West Java because the industry's contribution in the region to GRDP is relatively large. My research concluded that the effect of Knowledge Management on Intellectual Capital was significant. The effect of Knowledge Management and Intellectual Capital on the performance of each Branch Office is significant. In this case intellectual capital played a role in mediating the effectÃ‚Â  of Knowledge Management to the Branch performance Offices of state-owned banks in West Java. The Branch offices conducting knowledge management continuously resulted the good intellectual capital, which would strengthen the role of knowledge management in improving the branch performance.